2015
DOI: 10.1016/j.cattod.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the metal precursor on the properties of Pt/CeO2/C catalysts for the total oxidation of ethanol

Abstract: . Toluene hydrogenation has been used to obtain an estimation of the platinum dispersion on the investigated catalysts. On the other hand, their catalytic behavior has been evaluated in the total oxidation of ethanol, selected as a VOCs probe molecule. A much higher catalytic activity and selectivity to CO2 was achieved with chlorinated catalysts. This behavior has been correlated with a high platinum dispersion and a strong metal-CeO2 interaction in these catalysts which promotes their redox properties. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…In this sense, Pt/CeO 2 is a promising catalyst for the water-gas shift reaction (WGS). [1][2][3][4][5][6][7][8][9] Supported metal catalysts are traditionally prepared by impregnating a support material with the metal precursor solution, followed by calcination at a relatively elevated temperature and/or reduction under hydrogen (generally above 300 o C). The resulting metal particles are usually heterogeneously dispersed, with a broad particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Pt/CeO 2 is a promising catalyst for the water-gas shift reaction (WGS). [1][2][3][4][5][6][7][8][9] Supported metal catalysts are traditionally prepared by impregnating a support material with the metal precursor solution, followed by calcination at a relatively elevated temperature and/or reduction under hydrogen (generally above 300 o C). The resulting metal particles are usually heterogeneously dispersed, with a broad particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The elimination of aromatic products is significant in both the petroleum industry and environmental protection . These compounds can cause several health problems such as damages to the central nervous system and carcinogenic effects after prolonged exposure . To reduce the harmful effects of these compounds in the environment and humans, especially benzene, toluene, and xylene that are recognized as the most dangerous air pollutants , the catalytic hydrogenation reaction as an abatement technology for the elimination of these pollutants has aroused great attention .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1b shows the FTIR spectra for TiO 2 /manganese composite with varying manganese and sintered at 1200 o C. For all samples, the band (peak 1) located at 484.1 cm -1 indicates the presence of α-Mn 2 O 3 phase. The peak 2 that appears at 533 cm-1 corresponds to the Mn-O-Ti vibrational mode [7]. The peak 3 at 696 cm -1 can be assigned to Ti-O vibrational modes of rutile.…”
Section: Methods For Characterization Of the Synthesized Tio 2 -Manganmentioning
confidence: 96%
“…Manganese ores can be used for doping TiO 2 due to their unique structures, uniform pores, and channels. In a previous study, Reddam et al, [7] have investigated the particles size and BET surface area of rutile of TiO 2 /manganese composite at 600 o C. It has been found that the sizes of the rutile crystallites decrease from 41.35 to 31.01 nm for undoped TiO 2 and TiO 2 /manganese composite, respectively. Paul et al, [8] have prepared TiO 2 /manganese composite with 5 wt% manganese.…”
Section: Introductionmentioning
confidence: 99%